Exposure to Tramadol During Early Pregnancy and Risk of Spontaneous Abortion or Major Congenital Malformations. Issue 4 (10th April 2022) - Sørensen, Anne Mette Skov; Noergaard, Mia Muusfeldt; Gotfredsen, Ditte Resendal; Kjærbye-Thygesen, Anette; Jimenez-Solem, Espen; Askaa, Bjarke; Poulsen, Henrik Enghusen; Horwitz, Henrik; Andersen, Jon Trærup
Abstract : Exposure to tramadol during early pregnancy does not appear to be associated with an increased risk of spontaneous abortion or major congenital malformations. Abstract : OBJECTIVE: To investigate whether exposure to tramadol during early pregnancy is associated with an increased risk of spontaneous abortion or major congenital malformations. METHODS: The study is a nationwide cohort study including all registered pregnancies in Denmark between January 1, 1997, and December 31, 2016. The Danish National Prescription Register was used to identify maternal exposure to tramadol. Pregnancies with maternal exposure to tramadol were matched with pregnancies without maternal exposure to tramadol in a ratio of up to 1:4 using propensity scoring. The primary outcomes were spontaneous abortion and major congenital malformations. Cox proportional hazards regression was used to estimate the hazard ratios (HRs) of spontaneous abortion, and log binominal models were used to estimate the relative risk ratios (RRs) of major congenital malformations. RESULTS: A total of 36, 467 (tramadol exposure n=7, 310) and 18, 907 (tramadol exposure n=3, 796) pregnancies were included in the analyses of spontaneous abortion and major congenital malformations, respectively. Spontaneous abortion occurred in 893 (12.2%) pregnancies with maternal exposure to tramadol and in 3, 471 (11.9%) pregnancies without maternal exposure to tramadol (HR 1.06, 95% CI 0.99–1.14). A major congenital malformation occurred in the offspring of 151 (4.0%) pregnancies with maternal exposure to tramadol, compared with 579 (3.8%) in pregnancies without maternal exposure to tramadol (RR 1.04, 95% CI 0.87–1.24). CONCLUSION: Exposure to tramadol during early pregnancy does not appear to be associated with an increased risk of spontaneous abortion or major congenital malformations.